2021
DOI: 10.14295/bds.2021.v24i3.2481
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of 3d printing in dental applications

Abstract: Objective: To evaluate the applications of 3d printing /additive manufacturing (AM) in dental education & clinical dentistry and elaborate various 3d printing technologies, its benefits, limitations and future scope. Methods: Research papers on the application of 3d printing in dentistry were searched in Scopus and Pubmed and studied using bibliometric analysis.  This review briefly describes various types of 3d printing technologies with their accuracy, use of different materials for 3d printing and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Among different treatment options to replace a congenitally missing tooth, the dental implant is the main approach of dentists with different specialties [17]. Previous studies have demonstrated mechanical advantages regarding the presence of porosities in the titanium implant…”
Section: Discussionmentioning
confidence: 99%
“…Among different treatment options to replace a congenitally missing tooth, the dental implant is the main approach of dentists with different specialties [17]. Previous studies have demonstrated mechanical advantages regarding the presence of porosities in the titanium implant…”
Section: Discussionmentioning
confidence: 99%
“…Additive manufacturing (AM) processes, also known as 3D printing, are present in several areas, ranging from small implants to large vehicle parts, passing through branches such as medicine and dentistry. [1][2][3] The solutions presented by these technologies are viable because they are customizable and low-cost. 4 Customization is an essential factor in the health area due to the complexity of human beings, and it is estimated that in the future, hospitals will have bioprinters for transplant demands.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) processes, also known as 3D printing, are present in several areas, ranging from small implants to large vehicle parts, passing through branches such as medicine and dentistry 1–3 . The solutions presented by these technologies are viable because they are customizable and low‐cost 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The dental models obtained with 3D printing have been used in dental education for some time. Deployment of 3D scanners, of CBCT and of 3D printers has enabled the precise replication of real anatomical structures, achieving simulated dental models having a real clinical correspondent, which can be successfully used in dental education [ 34 , 35 ] The combination of traditional simulation techniques with digital simulation broadens the educational possibilities towards decision-making training and deliberate practice, which are less possible in traditional settings.…”
Section: Introductionmentioning
confidence: 99%